Surf's up, spongebob! ebook - Nickelodeon Publishing (SpongeBob SquarePants., 2011)
SpongeBob SquarePants learns to hang ten in this rad surfing-themed story that ties in with the primetime movie event airing in April 2009! SpongeBob eagerly accepts Sandy's invitation to go surfing at Goo Lagoon—until he realizes he doesn't know how to surf! What will he do? It's Patrick to the rescue as he shows SpongeBob how to ride the waves, right in their backyard. When he meets Sandy the next day, SpongeBob nervously makes his way out into the water and tries to break his surfboard so he wouldn't have to surf. But then he gets caught up in a huge wave, and he has no choice but to wipe out—or does he?